Potensi Senyawa Turunan Xanton dari Kulit Buah Manggis (Garcinia mangostana L.) Sebagai Inhibitor Protein Mycobacterium tuberculosis: Studi In Silico - Maftucha, Nissa; Manalu, RosarioTrijuliamus; Amelia, Rika; Cordia, Petra; Bupu, Regina (Pharmaceutical Journal of Indonesia, 2022)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis infection that attacks the lungs. Tuberculosis is a dangerous disease that can cause death. In overcoming it, a safe and effective treatment is needed so that this disease can be cured. The purpose of this study was to determine the potential activity of the active compounds derived from xanthones contained in the mangosteen rind as an inhibitor of Mycobacterium tuberculosis protein with the comparison compound Isoniazid. The active compounds used in this study were α-mangostin, β-mangostin, γ-mangostin, garsinon, gartanin, and 8-deoxygartanin. This research uses the molecular docking method with Yasara, MarvinSketch, PubChem, PDB, and Plants 1.1 software. The results showed that the Gibss energy produced by each test ligand had a difference value, either lower or higher than the native ligand protein of Mycobacterium tuberculosis. Lipinski screening was done to make it easier to determine a molecule or compound based on its permeability and absorption properties. The results showed that gartanin and 8-deoxygartanin complied with Lipinski's rules. Prediction of pharmacokinetic properties and toxicity was carried out using the pkCSM website and can be concluded that gartanin and 8-deoxygartanin compounds have good pharmacokinetic properties and low toxicity.